Clip-plate versus suture-anchor in double-door laminoplasty for degenerative cervical myelopathy: Protocol for a multicenter, non-inferiority, randomized controlled trial - Kentaro Yamada; Kenichiro Sakai; Takashi Hirai; Kazuyuki Fukushima; Takuya Takahashi; Yu Matsukura; Satoru Egawa; Hiroaki Onuma; Motonori Hashimoto; Akihiro Hirakawa; Yoshiyasu Arai; Toshitaka Yoshii (PLoS ONE, 2026)
Background Degenerative cervical myelopathy (DCM) is a leading cause of spinal cord dysfunction. While cervical laminoplasty (LAMP) is the standard treatment, the optimal fixation method for the opened lamina, specifically between the conventional suture-anchor method and the modern plate system, remains debated. Although clip-plates offer rigid fixation for the opened lamina, they are associated with higher costs and potential complications such as lamina reclosure due to screw dislodgement or hinge fracture. This study aims to verify the non-inferiority of the suture-anchor method compared to the clip-plate method in double-door LAMP. Methods This is a multicenter, open-label, non-inferiority randomized controlled trial. A total of 216 patients with DCM (cervical spondylotic myelopathy [CSM] or ossification of the posterior longitudinal ligament [OPLL]) will be recruited from three high-volume spine centers in Japan. Participants will be randomized (1:1) to undergo double-door LAMP using either clip-plates (control group) or suture-anchors (experimental treatment group). The primary endpoint is the recovery rate of the Japanese Orthopaedic Association (JOA) score at 1 year postoperatively. Secondary endpoints include operative time, blood loss, clinical assessments (EQ-5D-5L, visual analog scale [VAS], and neck disability index [NDI]), radiological outcomes (cervical spinal alignment, lamina retention rate, hinge fracture, bone union, and MRI findings), direct medical costs, and perioperative complications. Conclusions We hypothesize that the suture-anchor technique is non-inferior to the clip-plate system regarding neurological recovery and laminar stability. By rigorously comparing these techniques, this trial seeks to establish high-level evidence for a surgical strategy that maintains clinical standards while potentially reducing healthcare costs. Trail registration Japan Registry of Clinical Trials (jRCT) jRCT1032250437